Kajian Data Envelopment Analysis (DEA) Untuk Analisis Tingkat Efisiensi Wilayah dan Kota - Krishna Nur Pribadi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2000)
The study is an assessment on Data Envelopment Analysis (DEA) method as a tool to analyze region in order to assess the district and municipality region efficiency rate. The study will cover DEA basic concept, CCI? model, BCC model and return to scale.